FLOOD MODELING OF THE VUKA RIVER SECTION UPSTREAM OF ITS CONFLUENCE WITH THE DANUBE RIVER (Advances in Civil and Architectural Engineering, 2021)
In this paper, a section of the Vuka River from its confluence with the Danube River in Vukovar to 3 + 630 rkm was modeled. The possibility and size of floods in the surrounding area were analyzed for different return periods (2, 5, 10, 50, and 100 yrs). Although the high-water levels of the Danube River are lower than the terrain elevation of Vukovar, they cause backwater in the Vuka River and in its tributary, the Bobotski canal. In that indirect way, the surrounding area is endangered and the efficiency of drainage systems is reduced. The existing riverbed of the analyzed Vuka River section was digitalized based on a digital terrain model using the geographic information system (GIS) software ArcGIS and the HEC-GeoRAS toolbar. A mathematical model of the steady-state flow of the Vuka river section using the digitized riverbed was executed in the HEC-RAS software using different return periods. The obtained velocities and water levels were analyzed using HEC-RAS, and the sizes of the flooded areas were calculated and observed in ArcGIS.